PENGARUH SALINITAS TERHADAP PERTUMBUHAN UDANG VANAME (LITOPENAEUS VANNAMEI): Effect of Salinity on Growth Vaname Shrimp (Litopenaeus Vannamei) - Pebrianto, Djodi Harfi; Sumahiradewi, Luh Gede; Rahmawati , Aryani; Rizal, Lalu Samsul (Al-Qalbu: Jurnal Pendidikan, Sosial dan Sains, 2023)
The aim of this research was to determine the effect of salinity on the growth of vaname shrimp (Litopenaeus vannamei). This study used an experimental method with a completely randomized design (CRD) consisting of 4 treatments and 3 replications. The treatments were P1 (salinity 20 ppt), P2 (salinity 25 ppt), P3 (salinity 30 ppt), P4 (salinity 35 ppt). Young adult vaname shrimp are spread in a tub with a density of 2 4 tails . The parameters observed were absolute weight, specific growth rate, absolute length, life span, and water quality.The results showed that the difference in salinity affected the growth of vaname shrimp (F count> F table). At 35 ppt salinity gave the highest yield on the absolute weight growth of vaname shrimp of 4.30 g, specific growth rate of 2.35% day- 1 , absolute length 4.10 cm, and survival of 97%. Water quality that is suitable for the maintenance of vaname shrimp is temperature 31 ℃, DO 5 ppm and pH 7